Limnology and water quality in La Plata basin (South America) – Spatial patterns and major stressors - Nogueira, Marcos G. [UNESP]; Perbiche-Neves, Gilmar; de Oliveira Naliato, Danilo [UNESP]; Caglierani Casanova, Silvia M.; Roberto Debastiani-Júnior, José [UNESP]; Espíndola, Evaldo G. (Elsevier, 2021)
The La Plata Basin (LPB) is a continental river-system, extending across five countries in South America. The study intended to discriminate limnological and water quality macroscale patterns and the determinants. Samplings were performed at 44 points, including free-flowing river stretches and reservoirs, distributed along 3000 km, from tropical (18°S) to subtropical/temperate (33°S) latitudes, in summer and winter. In situ measurements and sample analyses included the water column (13 variables) and sediments (granulometry, nutrients, 36 pesticides, 13 metals, and bioassays for acute and chronic toxicity). Both natural factors – climate gradient, geological substrate, soil, floodplains, and human interference – river damming, metropolitan areas, and intensive agriculture, strongly influenced the results. Seasonality effects were pronounced in south of the LPB, associated with higher temperature amplitude, and in north of the LPB, in terms of marked precipitation distribution. Data sets were ordinated through principal component analyses, and spatial patterns were clearly evidenced. River impoundments determined higher deepness and transparency, lower temperature amplitude, and thermal and chemical stratification. Reservoir sediments presented higher organic matter and metal concentrations, fine sand, and silt. Higher natural turbidity, suspended matter and coarse sand sediments characterized the shallower free-flowing stretches, especially in the undammed Paraguay River. Recovery of the riverine conditions (Paraná and Uruguay Rivers) occurs with distance from dams due to the river's long courses. The variables indicating trophic conditions (phosphorus and nitrogen) were not clearly ordinated, but positioning of the most eutrophic LPB reservoir, under the influence of the São Paulo metropolis, was distinctive due to remarkably high chlorophyll a concentrations. Nutrients and conductivity were influenced by northern summer rains and tended to increase downstream, towards south latitudes. These variables were also locally influenced by urban agglomerations and by vast areas managed for commercial farming. Contamination with pesticides is widespread in LPB, but with higher incidence in the upper Paraná and middle Uruguay sub-basins. The same trend occurred for toxicity. A better understanding of macroscale processes brings a new perspective to transcend from local to a transboundary water management in the LPB.
Keywords: Free-flowing river stretches; Paraguay River; Paraná River; Reservoirs; Transboundary rivers; Uruguay River